Managing Your Wine Fermentation to Reduce the Risk of Biogenic Amine Formation - Smit, Anita Y.; Engelbrecht, Lynn; Du Toit, Maret (Frontiers in Microbiology, 2012)
Biogenic amines are nitrogenous organic compounds produced in wine from amino acid precursors mainly by microbial decarboxylation. The concentration of biogenic amines that can potentially be produced is dependent on the amount of amino acid precursors in the medium, the presence of decarboxylase positive microorganisms and conditions that enable microbial or biochemical activity such as the addition of nutrients to support the inoculated starter cultures for alcoholic and malolactic fermentation (MLF). MLF can be conducted using co-inoculation or an inoculation after the completion of alcoholic fermentation that may also affect the level of biogenic amines in wine. This study focused on the impact of the addition of complex commercial yeast and bacterial nutrients and the use of different MLF inoculation scenarios on the production of biogenic amines in wine. Results showed that the addition of complex nutrients to real grape must could potentially increase histamine concentrations in wine. The same experiment in synthetic grape must showed a similar trend for putrescine and cadaverine. The effect of different MLF inoculation scenarios was examined in two cultivars, Pinotage and Shiraz. Conflicting results was obtained. In the Shiraz, co-inoculation resulted in lower biogenic amine concentrations after MLF compared to before MLF, while the concentration was higher in the Pinotage. However, the production of biogenic amines was affected more by the presence of decarboxylase positive lactic acid bacteria than by the addition of complex nutrients or the inoculation scenario.